2023
DOI: 10.3390/foods12050966
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Commercial Fish Proteins’ Chemical and Sensory Properties for Human Consumption

Abstract: To stop overfishing and meet the protein needs of a growing population, more information is needed on how to use marine by-catches, by-products, and undervalued fish species for human consumption. Turning them into protein powder is a sustainable and marketable way to add value. However, more knowledge of the chemical and sensory properties of commercial fish proteins is needed to identify the challenges in developing fish derivatives. This study aimed to characterize the sensory and chemical properties of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
3
1
0
Order By: Relevance
“…The results agree with a past study by Partanen et al. (2023), as they identified that commercially available fish protein can have bitter and fishy attributes. Sourness can also be confused with bitterness by consumers (O'mahony, 1991) and that could explain why sour and bitter were both associated with marine collagens.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The results agree with a past study by Partanen et al. (2023), as they identified that commercially available fish protein can have bitter and fishy attributes. Sourness can also be confused with bitterness by consumers (O'mahony, 1991) and that could explain why sour and bitter were both associated with marine collagens.…”
Section: Resultssupporting
confidence: 93%
“…This study asked participants to consume marine collagen without being added to a food product, and this may explain why they found it to have an overall fishy characteristic. The results agree with a past study by Partanen et al (2023), as they identified that commercially available fish protein can have bitter and fishy attributes. Sourness can also be confused with bitterness by consumers (O'mahony, 1991) and that could explain why sour and bitter were both associated with marine collagens.…”
Section: Samplesupporting
confidence: 92%
See 2 more Smart Citations